The Construction and Application of Smart Teaching Model for Speaking in International Chinese Language Education: 国际中文智慧口语教学模式构建与应用 - Wenjing, Chen; Xujing, Chen (Mandarinable: Journal of Chinese Studies, 2024)
In the era of information technology transformation, education requires a digital transformation to meet the diverse learning needs of learners and to cultivate their digital competencies. International Chinese Smart Education is a crucial strategic initiative for advancing the digital transformation of education. There is an urgent need to develop effective teaching models to serve as a bridge between the theory of smart education and teaching practice. This study attempts to integrate the concepts of smart education with a Chinese oral language teaching model, leveraging educational technology to support both students' self-directed learning and teachers' instructional activities. A "three-stage, five-step" smart teaching model for oral language was constructed and applied in three rounds of practice. The survey indicates that this model significantly increased the speaking rate and total speaking time in oral classes. The effect of peer collaboration on learning was found to be nearly as effective as teacher-led instruction. There was a noticeable delay effect in the acquisition of written language and complex language structures, and learners' abilities to use interactive and discourse strategies were improved. However, the model also faced challenges in practice, such as increasing the burden on teachers for lesson preparation and widening the gap in skill levels among learners.